Long-Term Photo-Identification Reveals the Population Dynamics and Strong Site Fidelity of Adult Whale Sharks to the Coastal Waters of Donsol, Philippines - McCoy, Emer; Burce, Raul; David, David; Aca, Elson Q.; Hardy, Jennifer; Labaja, Jessica; Snow, Sally J.; Ponzo, Alessandro; Araujo, Gonzalo (Frontiers in Marine Science, 2018)
Donsol in the Philippines is the longest running community-based whale shark (Rhincodon typus) ecotourism site in Southeast Asia, with peak visitation in 2012 of over 27,000 tourists. In order to understand this aggregation and the importance of the area to whale sharks, dedicated photographic identification (photo-ID) research began in 2007. In-water photo-ID surveys were conducted from tourism boats, weather and operator permitting, from December to June between 2007 and 2016. Visual matches of the unique spot patterns of each individual shark were validated by the pattern-recognition software Interactive Individual Identification System (I3S), and on the online database Wildbook for Whale Sharks (www.whaleshark.org). A total of 1,985 photo-ID trips over 895 survey days resulted in 6,786 encounters with R. typus. Combined with encounters from both dedicated research and citizen science dating back to 1998, 479 individual whale sharks were identified, making up 44% of the known whale shark population in the Philippines (n = 1,095). Of these, photographs of the pelvic region confirmed the sex for 158 males and 22 females. Visual size estimates ranged from 2 to 10 m (mean ± S.D = 6.5 ±1.6 m). Maturity in males (LT50) was estimated at 6.8 ± 0.2 m total length, with 53% of males considered mature. Annually, the total number of individuals sighted varied between 15 and 185 ( mean ± S.D = 104 ± 55.53), with a recruitment of 3-90 new individuals yearly (mean ± S.D = 46.8 ± 36.29). Modelled residency using maximum likelihood methods suggested whale sharks spent 49.8 ± S.E. 14.5 (95% CI [32.3 – 78.6]) days in Donsol each season, with 47.1 – 60.8 whale sharks at any one time during the season. Twenty individuals were recorded through photo-ID at other sites across the Philippines. The extended residency of whale sharks at Donsol, paired with the presence of sexually mature animals and the economic value of the tourism industry, highlights the importance of Donsol for this endangered species.